An??lise de desempenho de redes cooperativas assistidas por buffer em dispositivos para redes B5G - Adanvo , Vignon Fidele (2021)
The fifth-generation (5G) technology and the requirements foreseen for the sixthgeneration (6G) are increasingly strict regarding reliability and transmission speed increase in mobile communication networks. Several proposals are being implemented and discussed to meet these requirements. Among these proposals, there is the use of a buffer in cooperative communication. Proper use of it allows users to experience highly reliable communication. In this dissertation, the use of buffer in devices is analyzed and different strategies for using it for cooperative networks are proposed. In particular, the proposed schemes are evaluated in a bidirectional network and a cognitive network with the Non-orthogonal multiple access (NOMA) technique in terms of the outage probability. First, a bidirectional cooperative network scheme with a hop composed of two transceiver and a relay is considered. It investigates the use of buffer both in the relay and in the source with different strategies. Among the proposed strategies are the use of a single buffer in the relay and the use of a buffer in all nodes of the bidirectional network. For the proposals presented, the impact of the transmission power, the transmission rate and the position of the relay in relation to the transmitter in terms of outage probability is evaluated. Less outage probability is obtained in relation to existing strategies. For the bidirectional network analyzed, an algorithm was proposed where an increment in the number of packets received in each time slot was achieved. Second, a cognitive underlay network scheme based on the NOMA technique using buffer and link state assisted relay selection is considered. Better system performance in terms of outage probability was achieved with an adequate choice of power allocation factor in the retransmission phase. In general, for the investigated scenarios, a better system performance in terms of outage probability was achieved with an adequate choice of buffer capacity and the location of the relay(s).